Peer Assessment in EFL Oral Presentation: Implementation and Students’ Perceptions in Indonesian Senior High School - Surya Dita; Muhammad Nur Akbar Rasyid; Wiwiek Wahyuni (Hasanuddin University, 2026)
Oral presentations are one of the most challenging speaking activities for EFL learners, but assessment in most Indonesian high school classes is still teacher-centered, which limits students’ active participation in the evaluation process. This study investigates the implementation of peer assessment in EFL oral presentation activities at senior high school in South Sulawesi, Indonesia, and explores students’ perceptions of its use. Using a qualitative case study design, this research involved one EFL teacher and 18 grade XI students as participants. Data were collected through classroom observations, semi-structured interviews with six purposively selected students, and document analysis of completed peer assessment rubric form. The findings show that peer assessment was successfully carried out through three structured phases: preparation before the assessment, active participation during the presentation, and filling out the rubric along with collecting written feedback. A simple rubric focusing on three aspects Delivery, Content, and Language Use proved to be practical and manageable for senior high school students. However, its implementation also presented some challenges, including friendship bias, limited evaluator knowledge, divided attention, and difficulties in writing feedback in English. Despite these challenges, student generally perceived peer assessment positively, reporting reduced speaking anxiety, enhanced self-reflection, and increased motivation to improve their English-speaking skills. These findings show that peer assessment, when supported with clear guidance and students-friendly rubrics, can be an effective and sustainable formative assessment strategy in EFL oral presentation classes, especially in large classes where personalized teacher feedback is limited.